Is Innovation the Missing Link in the Competitive Advantage of Indonesia's Small and Medium Enterprises in the Fashion Industry? - Fedrerika Fedrerika; Gracia Ongkowijoyo (Petra International Journal of Business Studies, 2024)
This study focuses on how SMEs in the fashion industry in East Java relate to one another in terms of entrepreneurial orientation (EO), market orientation (MO), innovation (INNO), and competitive advantage (CA). Using a quantitative technique and Google Forms to collect data, 130 respondents from SMEs in the fashion business in East Java were selected. This study aims to understand how EO and MO drive INNO and affect CA. The results show that, although EO encourages innovation, it does not immediately improve competitive advantage. Rather, MO and INNO have a more significant impact on CA, highlighting the significance of market knowledge and ongoing product innovation in achieving competitive advantage. This finding implies that modifying strategies can strengthen competitive positioning in response to market conditions. Limitations regarding regional focus and unanalyzed external factors highlight the need for future studies to expand their reach and evaluate other contextual influences.